FAKTOR – FAKTOR YANG MEMPENGARUHI KEPUTUSAN PETANI UNTUK MENANAM PADI SAWAH DI DESA BALUNIJUK KECAMATAN MERAWANG KABUPATEN BANGKA: FACTORS THAT INFLUENCE FARMERS DECISION TO PLANT RICE IN BALUNIJUK VILLAGE MERAWANG DISTRICT BANGKA REGENCY - Wahyuni, Sri; Evahelda, Evahelda; Setiawan, Iwan (Jurusan Agribisnis, Fakultas Pertanian, Perikanan dan Kelautan Universitas Bangka Belitung, 2020)
This study aims to describe the rice farming that occurred in Balunijuk Village, analyze the factors that Influence Farmer Decision to plant field rice and calculate the contribution of rice planting to the household food needs of field rice farmers in Balunijuk Village, Merawang District. The time and place of this research was conducted in January 2019 until July 2019 in Balunijuk Village, Merawang District, Bangka Regency. The research method used was a survey method. While the sampling method used in this research is the Proportionate Stratified Random Sampling method, which is a sampling technique if the population has heterogeneous member and proportional strata with a sample size of 78 people. Methods of data analysis using descriptive qualitative, binary logistic regression analysis and quantitative descriptive. The results showed that 1) Planting of field rice in Balunijuk Village, Merawang District, Bangka Regency began in 2016 with the government's effort to improve the welfare of the community in a program to create a strong agriculture, especially in the Special Efforts of Corn and Soybean. Land availability, capital assistance from the government and farming experience in growing rice are the reasons for farmer to plant rice in Balunijuk Village. 2) Factors that significantly affect the decision of farmer to plant field rice are the level of education, the number of family dependents, farming experience and capital availability. 3) The contribution of wetland rice farming to the fulfillment of family food needs is an average of 8.71 percent from Rp. 1,054,433 per annum